Chapter La comprensione del testo digitale e cartaceo in età scolare: il ruolo delle Funzioni Esecutive - Ruffini, Costanza (Studies on Adult Learning and Education, 2022)
The use of digital devices in education is increasing. The literature, however, reveals a disadvantage of digital compared to paper in performing specific learning tasks, in particular text comprehension, which is probably sustained by a different cognitive load and a tendency to use digital for superficial and fast reading. The present study investigates possible differences between paper and digital text comprehension in children of school-age by analysing the role of Executive Functions (EF) as mediating factors in performance. 175 children in 3rd, 4th and 5th grade were assessed for text comprehension in the two modes and assessed with EF tests. The results show that there are no differences between digital and paper text comprehension. However, dividing the sample into children with low and children with high levels of text comprehension, the former group is seen to benefit from digital compared to the latter group, which shows an opposite trend. Furthermore, the low performers score worse than high performers in the EF measures which show a mediating role between performance level and differences between paper and digital modes in text comprehension. The present study has important educational implications for the use of digital devices in education.